E-Module problem-based learning on chemical equilibria to improve students’ higher-order thinking skills: an analysis - Nur Syuhada Rusli; Nor Hasniza Ibrahim; Chuzairy Hanri; Johari Surif (International Journal of Evaluation and Research in Education (IJERE), 2024)
This study aimed to identify the specifications for developing a problem-based learning e-module for chemical equilibria to increase students’ higher-order thinking skills (HOTS). A qualitative approach with a semi-structured interview involving eight participants from form six teachers in Penang was utilized. The interview results were analyzed using NVivo 12 software by dividing the transcripts into several codes based on a thematic analysis approach. Four broad themes emerged from the need analysis interviews: i) the importance of chemical equilibria; ii) problems in teaching and learning chemical equilibria; iii) teaching strategy; iv) desired improvement. The findings of this study showed that the topic of chemical equilibria in form six syllabus is an important topic for students to master. Still, it is the most challenging concept for both students and teachers. Findings of the interviews also found that teachers need an e-module integrated with problem-based learning due to the lack of teaching resources, the content of the syllabus, and the lack of students’ thinking skills. Besides, teachers suggest variegating the content, strategies, and technology to develop the modules. These findings indicate that teachers are still unsatisfied with the existing teaching materials and strategies and, therefore require an e-module to meet their needs. All themes and codes of the findings are summarized using schematic diagrams. The results of this study are essential in designing and developing the e-module integrated with problem-based learning for the topic of chemical equilibria, which can be implemented and positively increase the HOTS level among form six students.